Design of Environmental Monitoring and Alarm System Based on Microcontroller - Chen, Peng (Journal of Theory and Practice of Engineering Science, 2024)
With the development of society, the improvement of science and technology, and the continuous optimization of production and life, people's living standards are also constantly improving. Therefore, people are starting to pay more and more attention to the comfort level of indoor environment. Housing is not only a place for family reunion and living, but also an important material guarantee for people's lives. However, with the rampant use of decoration materials and the increasing popularity of daily necessities, the hidden dangers of the living environment have greatly increased. Indoor environmental pollution has become one of the serious killers affecting modern human health, seriously affecting people's production and life. Therefore, it is particularly important to monitor the indoor environment, which not only needs to sensitively detect the concentration of various harmful gases, but also has an alarm function to constantly remind of dangers. The main functions of this design include: Connecting the microcontroller with temperature, humidity, and gas sensors to achieve real-time collection and reading of indoor temperature and humidity values, as well as monitoring gas concentration, and achieving the expected results. The display circuit was designed using LCD. The buzzer alarm function was used to automatically alarm when the gas concentration and temperature/humidity values exceeded the set standard values. When the temperature and humidity exceed the limit, the LCD display can immediately prompt and combine with LED alarm. When the gas concentration exceeds the limit, LED alarm is used.